Neue Sachlichkeit : Aquarelle Zeichnungen und Druckgraphik 1919-1933 aus den Beständen der Städtischen Kunsthalle Mannheim. - Grote, L.; Hartlaub, G.F.; Heusinger von Waldegg, Joachim (München : Goethe Institut, 1982)
Beckmann, Max ; Carrà, Carola ; Coubine, Othon ; Davringhausen, Heinrich Maria ; Dix, Otto ; Fuhr, Xaver ; Gilles, Barthel ; Grosz, George ; Heise, Wilhelm ; Hofer, Karl ; Hubbuch, Karl ; Kanoldt, Alexander ; Kars, Georg ; Kretzschmar, Bernhard ; Lenk, Franz ; Lutz, Joachim ; Masereel, Frans ; Mense, Carlo ; Nebel, Kay H. ; Picasso, Pablo ; Radziwill, Franz ; Schlichter, Rudolf ; Schrimpf, Georg ; Sprauer, Hermann ; Stoecklin, Nikolaus ; Voll, Christoph
Neue Sachlichkeit : Aquarelle Zeichnungen und Druckgraphik 1919-1933 aus den Beständen der Städtischen Kunsthalle Mannheim, 1982
Duits
boek